Exploring the Potential of Traditional Congklak in the Development of Early Childhood Cognitive Abilities - Emi Matura; Quang Van Son; Yahya Che Lah (Cahaya Ilmu Cendekia Publisher, 2024)
Research objectives: This research aims : (1) To determine the existence of influence Early Childhood Cognitive Development at Kasih Bunda Kindergarten, South Aceh through traditional games cocky. (2) To determine the teacher's activities in developing the cognitive abilities of young children at the Kasih Bunda Kindergarten in South Aceh through the traditional congklak game. Methodology: This research is an experimental research with a pre-experimental design. The subjects of this research were students in group B1 of Kindergarten Kasih Bunda South Aceh for the 2018/2019 academic year with a total of 27 students as an experimental class. The data analysis technique was carried out using descriptive quantitative by comparing the average of pre-test and post-test data collected through observation. Hypothesis testing was carried out using the t-test from the results of the activity scale. Main Findings: The main findings of this study are comparison of average values before and after treatment. At tcount > ttable or 27.30 > 2.056 then Ho is rejected which means at the level of confidence 95% of the time there is a significant difference between the scores obtained from the initial test and the final test. Novelty / Originality of this research: The novelty of this research is the discovery of the use of traditional games, such as congklak. Where this game is not only played but can improve the cognitive abilities of young children in terms of recognizing the concept of numbers.